1999
DOI: 10.1093/bja/83.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Fatal nefopam overdose

Abstract: Nefopam is a non-opioid analgesic agent with a central mode of action involving activation of descending pain-modulating pathways and inhibition of synaptosomal uptake of hydroxytryptamine, norepinephrine and dopamine. Adverse effects during therapeutic use and after overdose of nefopam are known to involve the central nervous system (confusion and convulsions), the cardiovascular system (tachycardia and palpitations) and the kidneys (oliguria and renal failure). We report a death after nefopam overdose in a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…(1,27,28). To our knowledge, there have been only two cases of fatal nefopam overdosage previously reported in the literature (Table I) (29,30). Both followed a voluntary, massive ingestion of nefopam tablets and were clinically well-documented.…”
Section: Resultsmentioning
confidence: 92%
“…(1,27,28). To our knowledge, there have been only two cases of fatal nefopam overdosage previously reported in the literature (Table I) (29,30). Both followed a voluntary, massive ingestion of nefopam tablets and were clinically well-documented.…”
Section: Resultsmentioning
confidence: 92%
“…The neuropsychiatric and cardiovascular ADRs are mainly known as signs of overdose. They include confusion, convulsions, hallucinations, tachycardia, bundle branch block or cardiac arrest [8–11]. Three fatal cases after nefopam overdose, have been reported in the literature [8–10].…”
Section: Discussionmentioning
confidence: 99%
“…8 Life-threatening effects have been reported in relation to nefopam overdose, however, including rare fatal overdoses characterized by convulsions and arrhythmia. 26,27 An accidental overdose was reported in a 77-year-old man who developed acute neurological impairment and renal failure. 28 Overdose was unlikely in the present study, however, since a low dose was used and all patients were closely observed in the ICU after surgery.…”
mentioning
confidence: 99%